Effects of Teachers’ Participation in Management of Physical and Material Resources on Their Motivation, Kenya - Kingi, Petronilla M.; Kalai, Jeremiah M. (European Scientific Journal, ESJ, 2018)
Motivation is one of the many factors that contribute to employee performance. Teachers’ motivation in public secondary schools has been highlighted as one of the factors that contribute to employee performance (Matoke, Okibo & Nyamongo, 2015). There is however a dearth of literature on the effects of teachers’ level of participation in management of physical and material resources on their motivation. The purpose of this study was to investigate the effects of teachers’ levels of participation in management of physical and material resources on teachers’ motivation in public secondary schools in Kiambu, Machakos and Kajiado Counties, Kenay. The study sought to establish whether there was a significant relationship between the teachers’ level of participation in management of physical and material resources on teachers’ motivation in secondary schools. The study used Kurt Lewin change management model (1951) and Herzeberg Motivation Hygiene Theory (1959). Correlation design was adopted with a sample size of 58 principal and 345 subject teachers. Data was collected using questionnaires for the teachers and principals and self-administered observation guide. Stratified random sampling technique was used to get the sample size of the respondents. Validity was established through expert consultation and reliability determined using cronbach alpha. Means were computed to compare the teachers’ and principals’ opinions on the teachers’ level of participation in management of physical and material resources. Mean of below 2.00 was considered low level, mean between 2 to 3.5 was moderate whereas as mean above 3.5 was regarded high level. Independent t-test was used to establish whether there was a statistical mean difference between the teachers and school principals’ opinion on the teachers’ level of teachers’ participation in management of physical material resources. Simple regression analysis was carried out in order to establish the effect of teachers’ participation in the management of physical and material resources on their motivation. The study established that teachers were moderately involved in management of physical and material resources. The independent sample t-test results shows that there was a significant difference in the mean difference between the means of principals’ and teachers’ views on teachers’ participation in management of physical and material resources t (377) = -6.073, p = 0.00. The study revealed a statistical significant relationship between teachers’ level of participation in the management of physical facilities and their motivation ( = .399, p-value< .01).There is need to embrace participative structures that encourage teachers’ participation in management of physical facilities and material resources. Through such ventures the teachers will highly be motivated to work and consequently improving the quality of education in Kenya.